Nilai Pendidikan Tauhid dalam Film â€œMunafik 2â€ Karya Syamsul Yusof - Aminah, Dewi; Pasya, Rayi; Rahmawangsih, Yuli Altri (Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID), Ciamis, Jawa Barat, Indonesia, 2020)
This study aims to elaborate the values â€‹â€‹of Islamic education in the film